Análise de sinais de EEG após reabilitação com imagética motora em indivíduos pós-AVC - Silva, Lucas Coutinho Pereira da (2018)
Individuals after stroke may present sequelae, requiring use of motor rehabilitation techniques to improve functional recovery and life quality. Motor imagery (MI) has been used as a motor rehabilitation technique (MRI) after stroke. The present study investigated changes in electric cortical activity related to rehabilitation with conventional physiotherapy associated with MI in eight post-stroke hemiparetic individuals. EEG signal was processed using the event-related potential (ERP), Magnitude-squared coherence (MSC), event-related desynchronism and synchronism (ERD/ERS) and Permutation Entropy during motor task. The parameters were compared in two rehabilitation moments: one week before MRI (PRM) and one month after MRI (Follow-up). The results indicate a high variability of the cortical response among individuals. Only two individuals presented differences between analyzed moments, especially in the contralateral frontal and central regions. These individuals showed improvement in motor function, as assessed by Minnesota Manual Dexterity Test and motor activity log test. Future studies with a greater number of individuals and different EEG parameters are necessary to better understand the differences presented between PRM and Follow-up moments.